Clinicopathological significance of laminin-5γ2 chain expression in superficial esophageal cancer. Issue 5 (1st July 2014) - Ito, E.; Ozawa, S.; Kijima, H.; Kazuno, A.; Miyako, H.; Nishi, T.; Chino, O.; Shimada, H.; Tanaka, M.; Inoue, S.; Inokuchi, S.; Makuuchi, H.
Summary: The glycoprotein laminin 5γ2 chain (LN -5γ2) has recently become a focus of increased interest and investigation as a marker of invasion in gastrointestinal malignancies. We investigated the significance of LN -5γ2 expression as a prognostic factor in superficial esophageal cancer. The study population consisted of 87 patients who had undergone a transthoracic esophagectomy and three-field lymphadenectomy for the treatment of superficial esophageal cancer at Tokai University Hospital. Formalin-fixed, paraffin-embedded sections of the resected specimens were examined using immunohistochemical staining and hematoxylin and eosin staining to assess the correlations between the LN -5γ2 expression pattern and the clinicopathological factors (age, sex, T-factor, N -factor, ly-factor, v-factor, degree of differentiation, infiltrative growth pattern, tumor node metastasis classification of malignant tumors [TNM ] stage, etc.) and the patient outcome. The expression pattern of LN -5γ2 was classified into an extracellular type (E type), characterized by the staining of extracellular matrix such as the basement membrane and the stroma (31 cases, 35.6%), and a cytoplasmic type (C type), characterized by the staining of the cytoplasm in the cancer cells (56 cases, 64.6%). The expression pattern was not correlated with any of the clinicopathological factors that were assessed. However, univariate analyses of the survival analysis data showed that the N -factor ( P = 0.011), TNM stage ( P = 0.011), and LN -5γ2 C type ( P = 0.017) were prognostic factors. A multivariate analysis revealed that the N -factor ( P = 0.049) and LN -5γ2 C type ( P = 0.048) were prognostic factors. In the survival analysis, a univariate analysis of the 75 T1b cases also showed that the N -factor ( P = 0.048), TNM stage ( P = 0.048), and LN -5γ2 C type ( P = 0.029) were prognostic factors, while a multivariate analysis showed that the LN -5γ2 C type ( P = 0.035) was a prognostic factor. The C type expression of LN -5γ2, i.e. confined to the cytoplasm, was correlated with an unfavorable outcome among the patients with superficial esophageal cancer in the present series. Observation of the LN -5γ2 expression pattern may be useful for the diagnosis of highly malignant tumors.